Macroeconomic and Firm-Specific Determinants of Stock Liquidity in Nepal - Sharma, Kishan; Chand, Pawan; Guragain, Prashant; Yadav, Ritu; Jha, Sachindra (Nepalese Journal of Finance, 2025)
This study examines the macroeconomic and firm-specific determinants of stock liquidity in Nepalese commercial banks. Turnover ratio and Amihud illiquidity ratio are selected as the dependent variables. The selected independent variables are firm size, earnings per share, GDP growth rate, inflation rate, interest rate and leverage. The study is based on secondary data of 10 Nepalese commercial banks with 100 observations for the period from 2014/15 to 2023/24. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, Economic Review Report and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of macroeconomic and firm-specific factors on stock liquidity in Nepalese commercial banks. The study showed that firm size has a positive impact on Amihud illiquidity ratio and turnover ratio. It indicates that larger the firm size, higher would be the Amihud illiquidity ratio and turnover ratio. Similarly, earning per share has a positive impact on Amihud illiquidity ratio and turnover ratio. It indicates that increase in earnings per share leads to increase in Amihud illiquidity ratio and turnover ratio. However, inflation rate has a negative impact on Amihud illiquidity ratio and turnover ratio. It indicates that increase in inflation rate leads to decrease in Amihud illiquidity ratio and turnover ratio. Likewise, interest rate has a negative impact on Amihud illiquidity ratio and turnover ratio. It indicates that increase in interest rate leads to decrease in Amihud illiquidity ratio and turnover ratio. In contrast, GDP growth rate has a positive impact on Amihud illiquidity ratio and turnover ratio. It indicates that higher the GDP growth rate, higher would be the Amihud illiquidity ratio and turnover ratio. However, leverage has a negative impact on Amihud illiquidity ratio and turnover ratio. It indicates that increase in leverage leads to decrease in Amihud illiquidity ratio and turnover ratio.